Microfinance Institutions and Public Policy. (IMF Working Papers; Working Paper, 2002)
Many governments and nongovernmental organizations have adopted policies to promote the growth of microfinance institutions (MFIs). The appropriate level and form of support for MFIs are discussed in this paper on the basis of a review of key MFI characteristics. Governments are also responsible for the regulation of MFIs; here, some principles concerning the extent and coverage of MFI regulation and supervision are developed.